Reproduction in a polluted world: implications for wildlife. Issue 2 (August 2020) - Aulsebrook, Lucinda C; Bertram, Michael G; Martin, Jake M; Aulsebrook, Anne E; Brodin, Tomas; Evans, Jonathan P; Hall, Matthew D; O'Bryan, Moira K; Pask, Andrew J; Tyler, Charles R; Wong, Bob B M
Abstract : Environmental pollution is an increasing problem for wildlife globally. Animals are confronted with many different forms of pollution, including chemicals, light, noise, and heat, and these can disrupt critical biological processes such as reproduction. Impacts on reproductive processes can dramatically reduce the number and quality of offspring produced by exposed individuals, and this can have further repercussions on the ecology and evolution of affected populations. Here, we illustrate how environmental pollutants can affect various components of reproduction in wildlife, including direct impacts on reproductive physiology and development, consequences for gamete quality and function, as well as effects on sexual communication, sexual selection, and parental care. We follow with a discussion of the broader ecological and evolutionary consequences of these effects on reproduction and suggest future directions that may enable us to better understand and address the effects of environmental pollution.